Variety is the spice of life: Flying-foxes exploit a variety of native and exotic food plants in an urban landscape mosaic - Yabsley, Samantha H.; Meade, Jessica; Hibburt, Thomas D.; Martin, John M.; Boardman, Wayne S. J.; Nicolle, Dean; Walker, Melissa J.; Turbill, Christopher; Welbergen, Justin A. (Frontiers in Ecology and Evolution, 2022)
Generally, urbanization is a major threat to biodiversity; however, urban areas also provide habitats that some species can exploit. Flying-foxes (Pteropus spp.) are becoming increasingly urbanized; which is thought to be a result of increased availability and temporal stability of urban food resources, diminished natural food resources, or both. Previous research has shown that urban-roosting grey-headed flying-foxes (Pteropus poliocephalus) preferentially forage in human-modified landscapes. However, which land-use areas and food plants support its presence in urban areas is unknown. We tracked 9 P. poliocephalus roosting in Adelaide, South Australia, between December 2019 and May 2020, using global positioning systems (GPS), to investigate how individuals used the urban landscape mosaic for feeding. The most frequently visited land-use category was ‘residential’ (40% of fixes) followed by ‘road-side’, ‘reserves’ and ‘primary production’ (13-14% each). However, ‘reserves’ were visited four times more frequently than expected from their areal availability, followed by the ‘residential’ and ‘road-side’ categories that were visited approximately twice more than expected each; in contrast, the ‘primary production’ category was visited approximately five times less than expected. These results suggest that while residential areas provide most foraging resources supporting Adelaide’s flying-fox population, reserves contain foraging resources that are particularly attractive to P. poliocephalus. Primary production land was relatively less utilized, presumably because it contains few food resources. Throughout, flying-foxes visited an eclectic mixture of diet plants (49 unique species), with a majority of feeding fixes (63%) to locally indigenous Australian native species; however, in residential areas 53% of feeding visits were to non-locally indigenous species, vs only 13% in reserves. Flowering and fruiting phenology records of the food plants visited further indicated that non-locally indigenous species increase the temporal availability of foraging resources for P. poliocephalus in urban Adelaide. Our findings demonstrate the importance of residential areas for urban-roosting P. poliocephalus, and suggest that the anthropogenic mixture of food resources available in the urban landscape mosaic supports the species’ year-round presence in urban areas. Our results further highlight the importance of conserving natural habitats within the urban landscape mosaic, and stress the need for accounting for wildlife responses to urban greening initiatives.